Furfural Synthesis from d‐Xylose in the Presence of Sodium Chloride: Microwave versus Conventional Heating. Issue 16 (15th July 2016) - Xiouras, Christos; Radacsi, Norbert; Sturm, Guido; Stefanidis, Georgios D.
Abstract: We investigate the existence of specific/nonthermal microwave effects for the dehydration reaction of xylose to furfural in the presence of NaCl. Such effects are reported for sugars dehydration reactions in several literature reports. To this end, we adopted three approaches that compare microwave‐assisted experiments with a) conventional heating experiments from the literature; b) simulated conventional heating experiments using microwave‐irradiated silicon carbide (SiC) vials; and at c) different power levels but the same temperature by using forced cooling. No significant differences in the reaction kinetics are observed using any of these methods. However, microwave heating still proves advantageous as it requires 30 % less forward power compared to conventional heating (SiC vial) to achieve the same furfural yield at a laboratory scale. Abstract : Microwave adventure ! The dehydration of xylose to furfural in the presence of NaCl is investigated under microwave and conventional heating. The highest furfural yield of 76 % is obtained using 3.5 wt % NaCl at 200 °C. Microwave heating does not show a prominent effect on the reaction kinetics, but lowers the energy consumption compared to simulated conventional heating (using SiC vials) at similar heating rates.